Mental health care in Athens: Are compulsory admissions in Greece a one-way road?. (May 2017) - Stylianidis, Stelios; Peppou, Lily Evangelia; Drakonakis, Nektarios; Douzenis, Athanasios; Panagou, Aimilia; Tsikou, Kyriaki; Pantazi, Amalia; Rizavas, Yannis; Saraceno, Benedetto
Abstract: Involuntary hospitalization has long been a contentious issue worldwide. In Greece, the frequency of compulsory admissions is assumed to be alarmingly high; however, no study has systematically investigated this issue. In line with this, the present study aims to estimate the frequency of compulsory admissions in a psychiatric hospital and to explore its underpinnings. All individuals who were admitted to the Psychiatric Hospital of Attica during June–October 2011 were included into the study. Information about their socio-demographic and clinical characteristics as well as their previous contact with mental health services was obtained from interviewing the patient and his/her physician. Furthermore, information about the initiation of the process of compulsory admission as well as patient's referral upon discharge was retrieved from patients' administrative record. Out of the 946 admissions 57.4% were involuntary. A diagnosis of unipolar depression, high social support and previous contact with community mental health services were found to yield a protective effect against involuntary hospitalization. Moreover, 69.8% of civil detentions were instigated by close relatives and 30.2% ex officio. These two groups differed in patients' social support levels and in medication discontinuation being the reason for initiation of the process. Lastly, only 13.8% of patients were referred to community mental health services at discharge. Our findings suggest that civil detentions are deeply entrenched in clinical routine in Greece. Moreover, poor coordination among services and relatives' burden seem to contribute substantially to the elevated rates.